2000
DOI: 10.1074/jbc.m003114200
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin Induces ErbB-2 Degradation by Proteolytic Fragmentation

Abstract: Exposure of carcinoma cell lines to the antibiotic geldanamycin induces the degradation of ErbB-2, a coreceptor tyrosine kinase that is frequently overexpressed in certain tumors. Using ErbB-2 mutants expressed as chimeric receptors or green fluorescent protein fusion proteins, we report that the kinase domain of ErbB-2 is essential for geldanamycin-induced degradation. The kinase domain of the related epidermal growth factor receptor was not sensitive to this drug. The data further indicate mechanistic aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
68
1
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 31 publications
13
68
1
1
Order By: Relevance
“…The GA-induced cleavage of ErbB2, which has previously been observed in Western blots (Tikhomirov and Carpenter, 2000, 2001, could essentially be a result of proteolysis of internalized ErbB2 in the endosomal/lysosomal degrada- …”
Section: Erbb2 Is Cleaved At the Plasma Membranementioning
confidence: 99%
See 2 more Smart Citations
“…The GA-induced cleavage of ErbB2, which has previously been observed in Western blots (Tikhomirov and Carpenter, 2000, 2001, could essentially be a result of proteolysis of internalized ErbB2 in the endosomal/lysosomal degrada- …”
Section: Erbb2 Is Cleaved At the Plasma Membranementioning
confidence: 99%
“…Several studies have shown that endocytic downregulation of ErbB2 is impaired in cancer cells (Sorkin et al, 1993; Baulida et al, 1996;Wang et al, 1999;Hommelgaard et al, 2004;Austin et al, 2004;Longva et al, 2005), and ErbB2 can even transmit this property to the related epidermal growth factor receptor (EGFR; Muthuswamy et al, 1999;Wang et al, 1999;Worthylake et al, 1999;Haslekas et al, 2005). Inhibition of HSP90 (e.g., with geldanamycin [GA]) leads to increased internalization and lysosomal degradation of ErbB2 in a manner depending on proteasomal activity (Tikhomirov and Carpenter, 2000;Austin et al, 2004;Lerdrup et al, 2006). HSP90 inhibition also induces cleavage of the cytoplasmic part of ErbB2, resulting in a transmembrane 135-kDa ErbB2 and short-lived cytoplasmic fragments (Tikhomirov and Carpenter, 2000;Lerdrup et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP90 binds to the N-lobe of the catalytic tyrosine kinase domain of ErbB2, apparently independent of cellular stress. HSP90 has been shown to stabilize ErbB2, likely by preventing ubiquitinylation and proteosomal degradation [108,109]. HSP90 also limits both tyrosine kinase activity and heterodimer formation thus restraining excessive EGF signaling [110].…”
Section: Signal Attenuationmentioning
confidence: 99%
“…The molecular chaperone HSP90 stabilizes ErbB2 at the cell membrane and increased expression of HSP90 in breast cancer is associated with poor prognosis [108,112]. Inhibition of HSP90 with molecules such as geldanamycin leads to ErbB2 degradation and ultimately attenuation of signaling [109]. The in vivo utility of such an approach remains to be determined given the diverse functions of HSP90.…”
Section: Targeted Therapymentioning
confidence: 99%